Homology modeling and in vivo functional characterization of the zinc permeation pathway in a heavy metal P-type ATPase. (10th November 2018) - Lekeux, Gilles; Crowet, Jean-Marc; Nouet, Cécile; Joris, Marine; Jadoul, Alice; Bosman, Bernard; Carnol, Monique; Motte, Patrick; Lins, Laurence; Galleni, Moreno; Hanikenne, Marc
Abstract : Three-dimensional modeling of the HMA4 protein in Arabidopsis reveals the zinc permeation pathway across the plasma membrane, and mutations in the pathway alter zinc and cadmium transport differently in plants. Abstract: The P1B ATPase heavy metal ATPase 4 (HMA4) is responsible for zinc and cadmium translocation from roots to shoots in Arabidopsis thaliana . It couples ATP hydrolysis to cytosolic domain movements, enabling metal transport across the membrane. The detailed mechanism of metal permeation by HMA4 through the membrane remains elusive. Here, homology modeling of the HMA4 transmembrane region was conducted based on the crystal structure of a ZntA bacterial homolog. The analysis highlighted amino acids forming a metal permeation pathway, whose importance was subsequently investigated functionally through mutagenesis and complementation experiments in plants. Although the zinc pathway displayed overall conservation among the two proteins, significant differences were observed, especially in the entrance area with altered electronegativity and the presence of a ionic interaction/hydrogen bond network. The analysis also newly identified amino acids whose mutation results in total or partial loss of the protein function. In addition, comparison of zinc and cadmium accumulation in shoots of A. thaliana complemented lines revealed a number of HMA4 mutants exhibiting different abilities in zinc and cadmium translocation. These observations could be instrumental to design low cadmium-accumulating crops, hence decreasing human cadmium exposure.